PENGARUH SISTEM AKUNTANSI PENGGAJIAN TERHADAP KEPUASAN KARYAWAN PADA PT TIRAN GROUP CABANG BOMBANA - Riza, Anjeli; Turi, La Ode; Chairunnas, Arnadi (Komunitas Manajemen Kompetitif, 2025)
Anjeli Riza, the influence of the payroll accounting system on employee satisfaction at PT. Tiran Group Branch Bombana.This study aims to determine the influence of the payroll accounting system on employee satisfaction at PT Tiran Group Branch Bombana.This research uses a quantitative research method. The research population consists of employees of PT. Tiran Group Branch Kolaka, with a total of 40 respondents. The data collected in this study includes primary and secondary data. Primary data was obtained by distributing questionnaires to respondents, while secondary data was obtained from PT. Tiran Group's records. Data analysis techniques involved simple linear analysis using SPSS 30.The results indicate that the payroll system has a significant impact on employee performance, as the t-test value is less than the t-table (<0.001 < 0.05). It can be concluded that the payroll system coefficient of 0.535 at PT. Tiran Group. has a positive and significant impact on employee satisfaction. Based on the research results above, it shows that the variable of the payroll system at PT. Tiran Group Branch Bombana has a very positive influence on the variable of increasing employee satisfaction. This means that if a company wants its employees to perform at their best, the company must establish the best possible payroll system, which can improve the welfare of its employees, so that employees can be motivated to work more effectively. Consequently, the company will also benefit and perform better in achieving the goals it wants to accomplish in the future. Keywords: accounting system, payroll, wages, employee satisfaction.